Equity versus efficiency? Evidence from three-person generosity experiments - Werner Güth; Kerstin Pull; Manfred Stadler; Agnes Stribeck (Games, 2010)
In two-person generosity games, the proposer's agreement payoff is exogenously given, whereas that of the responder is endogenously determined by the proposer's choice of the pie size. In three-person generosity games, equal agreement payoffs for two of the players are either exogenously excluded or imposed. We predict that the latter crowds out - or at least weakens - efficiency seeking. Our treatments rely on a 2x3 factorial design, differing in whether the responder or the third (dummy) player is the residual claimant and whether the proposer's agreement payoff is larger, equal, or smaller than the other exogenously given agreement payoff.
Keywords: 330; generosity game; equity; efficiency; experiment